Myanmar Health Financing System Assessment - Teo, Hui Sin; Cain, Jewelwayne Salcedo (World Bank, Washington, DC, 2018)
Myanmar’s National Health Plan (NHP) for 2017-2021 has laid out the vision of achieving Universal Health Coverage (UHC) by 2030. The NHP aims to improve the delivery of health services and financial protection for Myanmar people through substantial investments in frontline service delivery units and through a range of reforms in the health system, including on health financing. This report assesses Myanmar’s health financing system. The analysis is structured around three main sets of questions: (i) Who pays for health in Myanmar? Given that the government needs to invest more in the health sector, where could (or should) the money come from; (ii) Are prepaid and pooled funds for health sufficient and equitable? What additional pooling arrangements could Myanmar consider; and (iii) What key steps and reforms are needed for Myanmar to develop the capabilities of a strategic purchaser in the medium term? This Health Financing System Assessment aims to inform health financing policy choices that the Government of Myanmar will need to make as part of the development and implementation of its Health Financing Strategy.